Insights into DNA hydroxymethylation in the honeybee from in-depth analyses of TET dioxygenase - Wojciechowski, Marek (The Royal Society, 2014)
In mammals, a family of TET enzymes producing oxidized forms of 5-methylcytosine (5mC) plays an important role in modulating DNA demethylation dynamics. In contrast, nothing is known about the function of a single TET orthologue present in invertebrates. Here, we show that the honeybee TET (AmTET) catalytic domain has dioxygenase activity and converts 5mC to 5-hydroxymethylcytosine (5hmC) in a HEK293T cell assay. In vivo, the levels of 5hmC are condition-dependent and relatively low, but in testes and ovaries 5hmC is present at approximately 7–10% of the total level of 5mC, which is comparable to that reported for certain mammalian cells types. AmTET is alternatively spliced and highly expressed throughout development and in adult tissues with the highest expression found in adult brains. Our findings reveal an additional level of flexible genomic modifications in the honeybee that may be important for the selection of multiple pathways controlling contrasting phenotypic outcomes in this species. In a broader context, our study extends the current, mammalian-centred attention to TET-driven DNA hydroxymethylation to an easily manageable organism with attractive and unique biology.